A Novel Electrically Conductive Perylene Diimide‐Based MOF‐74 Series Featuring Luminescence and Redox Activity. Issue 5 (5th February 2022) - Scheurle, Patricia I.; Biewald, Alexander; Mähringer, Andre; Hartschuh, Achim; Medina, Dana D.; Bein, Thomas
Abstract : Metal‐organic frameworks (MOFs) featuring significant electrical conductivity constitute a growing class of materials, with intriguing possible applications as porous semiconductors or supercapacitors. If such features are combined with photoluminescence (PL), additional functionalities such as selective chemical sensing become accessible. Here, perylene diimide (PDI)‐based linear building blocks are incorporated into the MOF‐74 topology with the three metal ions Zn 2+, Mg 2+, and Ni 2+, resulting in a new series of MOFs, namely PDI‐MOF‐74(M). PDI derivatives are dye molecules exhibiting remarkable optical properties, high electron mobilities, as well as interesting redox behavior. However, PDI‐based 3D MOFs are very rare and to date were only reported once. The frameworks of the PDI‐MOF‐74(M) series exhibit high crystallinity, electrical conductivity, and show well‐defined redox activity. In addition, the frameworks of the series feature PL in the orange and red spectral regions. Herein, the series of electroactive MOF‐74 structures as well as the group of 3D PDI‐based MOFs is expanded, hence opening up the development of novel MOFs with promising optoelectronic properties comprising PDI building blocks. Abstract : Incorporation of a perylene diimide (PDI)‐based linear building block into the MOF‐74 topology, leads with the three metal ions Zn 2+, Mg 2+, and Ni 2+, to a new series of MOFs, namely PDI‐MOF‐74(M). The highly crystalline PDI‐MOF‐74(M) series exhibit electrical conductivity and show well‐defined redox activity. Additionally, the series feature photoluminescence in the orange and red spectral regions.